Functionalized Separators Boosting Electrochemical Performances for Lithium Batteries - Fan, Zixin; Chen, Xiaoyu; Shi, Jingjing; Nie, Hui; Zhang, Xiaoming; Zhou, Xingping; Xie, Xiaolin; Xue, Zhigang (Nano-Micro Letters, 2025)
The growing demands for energy storage systems, electric vehicles, and portable electronics have significantly pushed forward the need for safe and reliable lithium batteries. It is essential to design functional separators with improved mechanical and electrochemical characteristics. This review covers the improved mechanical and electrochemical performances as well as the advancements made in the design of separators utilizing a variety of techniques. In terms of electrolyte wettability and adhesion of the coating materials, we provide an overview of the current status of research on coated separators, in situ modified separators, and grafting modified separators, and elaborate additional performance parameters of interest. The characteristics of inorganics coated separators, organic framework coated separators and inorganic–organic coated separators from different fabrication methods are compared. Future directions regarding new modified materials, manufacturing process, quantitative analysis of adhesion and so on are proposed toward next-generation advanced lithium batteries. Highlights: 1 The commonly used modification methods for separator of lithium batteries are summarized, which include surface coating, in situ modification and grafting modification. 2 The adhesion of coating materials with the separators and wettability of the modified separators prepared from the three methods are compared. 3 The challenges and future directions of separator modification are provided.